Manual handling amongst physiotherapists: Analysis of intra-shift variations in pain, fatigue and movement. - Rothmore, Paul; Hewitt, Tony; Dickson, Cameron; Nguyen, Tam (Work, 2023)
BACKGROUND: Manual handling injuries amongst physiotherapists are common and the need to improve our understanding of causal influences is imperative. OBJECTIVE: The objective was to determine whether intra-shift variations in manual handling task performance occurred in our cohort, which may inform mechanisms underpinning related injuries. METHODS: We used motion capture, force plate dynamics and electromyography to identify variations in task performance, loading forces and muscle activity, during the performance of one static and one dynamic standardized manual handling task, pre- and post-shift, by 40 physiotherapists. Participants also rated their pain and fatigue on a visual analogue scale (VAS). Statistical analysis utilised paired samples Student's t tests. RESULTS: Significant differences were seen in the EMG activity in the quadriceps during the static task only. No significant differences were seen for any of the kinematic variables. Significant differences in fatigue (p < 0.005) were seen between the pre- and post-shift sessions. Notably, there were significant differences in pain between the pre- and post-shift sessions in the static (p < 0.01) and dynamic tasks (p < 0.05). This increase in pain was at a level which impacted on function. CONCLUSION: Whilst significant variations in task performance were not observed, our findings indicate that physiotherapists frequently experience task-related pain towards the end of their shift. Contemporary research indicates that frequent transient low back pain may transition to a chronic disabling condition, as such we posit that the effects of intra-shift pain, and its causative factors, should be more widely considered in a 'whole-of-job' approach to mitigating risk in this demographic.